Electrochemically Activated Water Police Crops With Microelement Solution Processing Before Planting (Texas Journal of Agriculture and Biological Sciences, 2024)
The article presents the results of preliminary studies conducted on the treatment of pumpkin seeds with a solution of microelements of electrochemically activated water before sowing and studying the effect on plant growth and development.